Rental housing discrimination and the persistence of ethnic enclaves - Mariano Bosch; M. Angeles Carnero; Lídia Farré (SERIEs - Journal of the Spanish Economic Association, 2015)
We conduct a field experiment to show that discrimination in the rental market represents a significant obstacle for the residential mobility of immigrants and contributes to the ethnic residential segregation observed in large cities. We employ the Internet platform to identify vacant rental apartments in different areas of the two largest Spanish cities, Madrid and Barcelona. We send emails showing interest in the apartments and signal the applicants' ethnicity by using native and foreign-sounding names.We find that, in line with previous studies, immigrants face a differential treatment when trying to rent an apartment. Our results also indicate that this negative treatment varies considerably with the share of immigrants in the area. In neighborhoods with a scarce presence of immigrants the response rate is 30 percentage points lower for immigrants than for natives, while this differential decays towards zero as the immigration share increases. This evidence indicates that discriminatory practices may perpetuate the spatial segregation of minority groups.
Keywords: J15; J61; 330; Immigration; Discrimination; Ethnic residential segregation